2016
DOI: 10.1590/0102-6720201600020003
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for Cholecystitis and Cholelithiasis in the State of Rio Grande Do Sul, Brazil

Abstract: Background: The cholelithiasis is disease of surgical resolution with about 60,000 hospitalizations per year in the Sistema Único de Saúde (SUS - Brazilian National Health System) of the Rio Grande do Sul state. Aim: To describe the profile of hospitalizations for cholecystitis and cholelithiasis performed by the SUS of Rio Grande do Sul state, 2011-2013. Methods: Hospital Information System data from the National Health System through morbidity list for cholelithiasis and cholecystitis (ICD-10 K80-K81). Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…For example, the Ministry of Social Development maintains an electronic database (“Cadastro Único,” CadUnico) for provision of social services, such as the Conditional Cash Transfer Program (BFP) and the Housing Program (MCMV). These databases, in combination with others, have been used to study social determinants of health and evaluations of social policies on health (Rasella et al, 2013; Nunes et al, 2016; Machado et al, 2018). Table 1 summarizes some details about the main databases publicly available from SUS and other governmental sources in Brazil.…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Ministry of Social Development maintains an electronic database (“Cadastro Único,” CadUnico) for provision of social services, such as the Conditional Cash Transfer Program (BFP) and the Housing Program (MCMV). These databases, in combination with others, have been used to study social determinants of health and evaluations of social policies on health (Rasella et al, 2013; Nunes et al, 2016; Machado et al, 2018). Table 1 summarizes some details about the main databases publicly available from SUS and other governmental sources in Brazil.…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
“…For those who had their benefits turned down but want to reapply and those who are already receiving a benefit, the information update is mandatory. The extensive coverage of this social registry, the availability of individually identified data, and the possibility of linking them to other health care databases, such as SIM/SINASC/SINAN, allow for designing individual level longitudinal studies to evaluate the impact of social protection programs on health outcomes (such as diseases, hospitalizations, and deaths) (Paim et al, 2011; Rasella et al, 2013; Nunes et al, 2016; Machado et al, 2016a) and has inspired the development of the 100 Million Brazilian Cohort (Pinto et al, 2017; Pita et al, 2018).…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
“…In the literature it is observed that the gallstones is rare in children, begins to be identified in adolescence; shows marked increase in incidence between 35-55 years and increases gradually after 55 years of age 4 . Emeline Caldana et al found in their study a very low incidence of cholecystitis and cholelithiasis in patients between 0-4 years, with zero mortality 16 . The number of operations should increase with age, as gallstones increases with it, but this did not happen; perhaps, the risk of cholelithiasis and the risk of being submitted to VLC differ because there is less symptoms in older ages.…”
Section: Discussionmentioning
confidence: 96%
“…We have read with interest the recently research published by Nunes EC et al 1 and we believe that this is a very interesting study considering how prevalent is gallbladder calculus disease in Latin America. However, we would like to make some comments, as there are some aspects that can be discussed.…”
mentioning
confidence: 85%